Analisis Antibakteri Ekstrak Pacar Kuku (Lawsonia Inermis L.) Sthaphylococcus Aureus Dengan Metode Turbidimetri - Nurul Janah, Fatimah; Nur, Achmad Vandian; Rahmasari, Khusna Santika; Mugiyanto, Eko (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2024)
The leaves of henna are commonly used by local communities to treat burns, inflammation, and skin diseases. This plant contains lawsone (2–hydroxy-1,4-naphthoquinone) and various phenolic glycosides, flavonoids, tannins, alkaloids, and quinones, which are believed to contain antibacterial activity. This study aims to determine whether ethanol extracts from the leaves and stems of henna exhibit antibacterial activity and to assess their inhibitory effects against Staphylococcus aureus. The methods employed in this study include maceration and turbidimetric analysis. The extraction method was maceration with 96% ethanol as the solvent. The antibacterial activity was tested using the turbidimetric method with extract concentrations of 15%, 25%, and 30%. Chloramphenicol was used as a positive control, and NaCl served as a negative control. The results revealed that the leaf extracts of henna exhibited antibacterial activity in the leaves and stems of henna nails by comparing the average absorbance values before and after incubation. At concentrations of 15%, 25% and 30% of the leaves of henna na na experienced shedding after incubation which showed that the growth of bacteria had been inhibited. Meanwhile, in the henna nail stem extract, the concentration of 15% decreased after incubation and the concentration of 25%, 30% showed an increase in absorbance value after the incubation process.